Epistemic lines of advanced scientific research - Salcedo Lucio, Francisco David (Revista Universidad de Guayaquil, 2010)
Research and development in Educational Informatics is a consolidated group that began in 2010. Its objective is to investigate the dialectical synergy of informatics in formal processes of critical-constructive learning at the higher education level, and to support the achievement of cognitive objectives for professionals in training in higher education, with an emphasis on effective metacognitive formation. Since 2010, research in classroom contexts and thesis work has focused on education through the contribution of significant and critical epistemic-constructive strategies, following a dialectic-critical and hermeneutic-dialectic approach in the use of Information and Communication Technologies in scientific-professional processes. By continuously strengthening and professionalizing the human talent of the research team, actively participating in local, provincial, regional, and national research events, and fostering cooperation between interdisciplinary and transdisciplinary groups for research and development in Educational Informatics, the group aims to maintain leadership in advanced scientific research applied to areas supporting formal education processes. Additionally, it seeks to achieve coverage in higher education and maintain its participation in reflection spaces related to the topic at both national and, if possible, international levels.